ITS2 AND trnH-psbA IN IDENTIFYING HIBISCUS SPECIES, MURRAYA PANICULATA AND MELALEUCA CITRINUS - Jordan, Issory Chavyn (2018)
The identification of plant species is still relevant today. It is used in ecology, medical field and for conservation efforts. DNA barcoding is a method able to provide a standardized and efficient tool for identification. It involves specific DNA sequences such as ITS2 and trnH-psbA known as DNA barcodes which are compared with known barcode sequences found on databases. Previous experiments to obtain ITS2 from Hibiscus resulted in poor quality sequence probably because of the heterogeneity of the barcode. One of the goals of this study was to see if the same problem exists in other members of the same clade, using Murraya panniculata, Hibiscus spp. and Callistemon citrinus as samples. Additionally, the effectiveness of trnH-psbA was assessed in the identification of the Roside clade. This study also attempted to identify a hibiscus species which had morphological characteristics which could not clearly identify it at species level. DNA was extracted using CTAB buffer followed by amplification of the markers by PCR after genomic DNA bands have been obtained on an agarose gel. It was hard to grind the leaves of the Hibiscus since foaming occurred. The amplification of the markers also required several attempts and modifications of sample concentrations. Nonetheless enough PCR products were successfully obtained for sequencing, and good quality sequences were obtained for all the samples. However, traces showed some multiple peaks at specific locations in the ITS2 sequences of Hibiscus rosa-sinensis and trnH-psbA sequences of M. paniculata. High mismatch ratios between the forward and reverse sequence were also encountered for these sequences and a consensus sequence could not be obtained using DNA BASER software. In these cases, only sequences from unidirectional reads were used. Using BLAST, the identification of the Hibiscus species and M. panniculata were ambiguous unlike C. citrinus. Maximum likelihood tree and neighbor joining tree using both markers could differentiate each species. Like the H. rosa-sinensis and M. panniculate, the unknown Hibiscus may be a hybrid; as the nuclear locus identified it as Hibiscus fragilis and the chloroplast loci identified it as Hibiscus syriacus.